A novel moisturizer extracted from freshwater macroalga [rhizoclonium hieroglyphicum (C.agardh) k tzing] for skin care cosmetic - Pimporn Leelapornpisid (2018)
© 2014, Chiang Mai University. All rights reserved. Our previous study demonstrated that the aqueous extract from freshwater macroalga Rhizoclonium hieroglyphicum (C.Agardh) K tzing (RW) contained mostly polysaccharides and amino acids which might play an important role as a skin moisturizer. Therefore, its moisturizing effect in pig skin model and human skin was compared with some well-known commercial moisturizers such as glycerin (G), propylene glycol (PG) and hyaluronic acid (HA). The RW cream was then formulated and investigated its physical properties, pH and viscosity as well as stability under various storage conditions. The skin irritation and clinical evaluation for skin moisturizing effect in healthy volunteers were also evaluated. Skin patch test using Finn chamber®and skin moisturizing measurement using Corneometer® were conducted in 30 healthy volunteers. The skin hydration was measured at before and after applying the RW cream and control creams (cream base, G, PG and HA creams) for 15, 30 min, 1 hour for a short-term effect and 1 week (twice daily) for long-term usage. Satisfaction test using questionnaire was also performed. The results revealed that the moisturizing effect on human skin of RW is very similar to hyaluronic acid and glycerin. From clinical evaluation, the skin hydration increased after using RW cream in both short-term and long-term usage and no skin irritation occurred. Interestingly, the moisturizing effect of RW cream was comparable to HA cream (p<0.05). More than 80% of the volunteers were satisfied with RW cream. In conclusion, the freshwater macroalga extract might be a promising natural skin moisturizer for skin care cosmetics.